A hybrid niobium-based oxide with bio-based porous carbon as an efficient electrocatalyst in photovoltaics: a general strategy for understanding the catalytic mechanism. Issue 24 (6th June 2019) - Wang, Chen; Yun, Sining; Fan, Qingyang; Wang, Ziqi; Zhang, Yangliang; Han, Feng; Si, Yiming; Hagfeldt, Anders
Abstract : A general strategy of understanding the catalytic mechanism for a high-performance bio-based porous carbon supported ZnNb2 O6 hybrid catalyst is illustrated. Abstract : Developing a high-performance catalyst and establishing a catalytic mechanism for understanding the catalytic activity are crucial to new generation photovoltaic technology. In this work, we present a feasible and general route to synthesize a bio-based porous carbon (BPC) supported ZnNb2 O6 hybrid catalyst with a unique network structure, providing an effective means for electron transport between the electrode and the external circuit. Benefitting from the synergistic effect of ZnNb2 O6 and BPC, a photovoltaic device assembled with the nanohybrid yields a power conversion efficiency of 8.83%, which is superior to that of pristine ZnNb2 O6 -based and conventional Pt-based cells (7.15% and 7.14%). Systematic electrochemical evaluations of the hybrid catalysts exhibit promising stability for practical application in photovoltaics. Contraposing the two vital functions of the counter electrode catalyst, collecting electrons and catalyzing I3 − reduction, we propose a general strategy to understand the potential catalytic mechanism from the band structure and surface adsorption by using first-principles density functional theory (DFT) calculations. The theoretical investigations clearly indicate that the splendid catalytic performance originates from the zero band-gap of surface metal atoms and the surface chemical adsorption interaction between I3 − and exposed metal atoms. The proposed general strategy in this work for synthesizing a hybrid material with a unique network structure and understanding the catalytic mechanism of the electrocatalyst can guide the design of expected catalytic nanohybrids applied in various energy fields.